Foreign language pronunciation, from theory to practice - Králová, Zdena (Cambridge Scholars Publishing, 2021)
This book comprehensively deals with foreign language pronunciation. It considers several essential issues, including the relationship between native and foreign language pronunciations, the problems of non-native learners when learning foreign language pronunciation and the factors that can positively or negatively affect its learning. The book analyses foreign language pronunciation from both the linguistic and pedagogical points of view. It will thus appeal to all foreign language learners, teachers, linguists, and methodologists.